Analisis Ekspor Minyak Mentah Indonesia - Adhani, Nadia; Lubis, Irsad (Economic Reviews Journal, 2024)
The type of research used in this research is descriptive research with a quantitative method approach. This research uses secondary data. Secondary data was obtained in the form of periodic data (time series) over a period of 30 years (1991-2021) with the analysis model used in this research being a multiple linear regression model with the OLS (Ordinary Least Square) method. The analysis tool used is the SPSS (Statistical Product and Service Solution) program. Sources of data collected in this research came from BPS (Central Statistics Agency), BPS Silastic, Bank Indonesia (BI), World Bank, Library Research. This research suggests increasing Indonesia's crude oil production to meet national and international demand as well as increasing Indonesia's crude oil exports so that it can help accelerate economic development.